Seroprevalence of BVD molecular detection of the virus in cattle and buffaloes and its risk factors in selected farms in Selangor and Sabah, Malaysia - Khalid, Nurulhidayah (2021)
Bovine viral diarrhoea virus (BVDV) is a single stranded plus sense RNA virus of Pestivirus genus under Flaviviridae family. Bovine viral diarrhoea (BVD) disease is manifested by diarrhoea and immunosuppression that exacerbates other respiratory diseases. BVDV seroprevalence in cattle was reported in Malaysia, but no BVDV antigen detected and isolated. Furthermore, there was no BVDV study conducted in buffaloes in this country. The objectives of this study were to determine the seroprevalence of BVDV, to isolate, identify, and molecularly characterized local BVDV, and to determine the risk factors of BVDV in cattle and buffaloes in the selected farms. Seroprevalence of BVDV was determined using commercial kit LSIVet™ Ruminant BVD/BD p80 kit-Serum/Milk (ThermoFischer Scientific, USA). The overall seroprevalence of BVDV was 28.2% (95% CI=22.1-35) and was significantly different between farms (P<0.01, χ2=67.172). Farm G, A, D, H and C have seroprevalence of 61.8%, 51.9%, 41.7%, 10.2%, and 10.0% respectively. Farm B and Farm F were seronegative. All serum samples of buffaloes were seronegative. The BVDV seroprevalence were significantly different between species (P=0.01, χ2=10.504). Seroprevalence of BVDV for both cattle and buffaloes were 24.8% (95% CI=19.3-30.9). The individual and management risk factors were determined by logistic regression analyses. Potential risk factors for BVDV seroprevalence were lactating animals (OR=2.244, 95% CI=1.163-4.331), intensive system (OR=5.914, 95% CI=2.147- 16.295), the use of AI (OR=17.723, 95% CI=7.101-44.234), has milking parlour (OR=2.151, 95% CI=1.096-4.224), shared pen for feeding (OR=7.729, 95% CI=2.065- 28.926), did not have employee in the farm (OR=3.958, 95% CI=1.718-9.120), have the employee staying inside the farm (OR=6.469, 95% CI=2.555-16.375), did not have separate vehicle drop off area (OR=5.957, 95% CI=1.938-18.32), did not restrict visitor access (OR=5.957, 95% CI=1.938-18.32). Only one sample positive (1/253) following RT-PCR targeting conserved 5'UTR region of BVDV. Thus, BVDV antigen prevalence was 0.40% (95% CI=0.0-2.2). UPM/MAL/BVDV/D17 was classified under subgenotype BVDV-1a as determined by the hypervariable E2 region of BVDV. Adaptation in bovine turbinate (BT) cell cultures produced cytopathic effects (cpe) but it was not specific to BVDV. In conclusion, BVDV is present and circulating in cattle but not in buffaloes. Since BVDV exists in many subgenotypes, it is imperative for Malaysia to control the entry of more BVDV subgenotypes by screening all the incoming cattle at all borders.